New radiation techniques in gynecological cancer. Issue 4 (1st June 2004) - Ahamad, A.; Jhingran, A.
Abstract : Radiation therapy has been a major therapeutic modality for eradicating malignant tumors over the past century. In fact, it was not long after the discovery of radium that the first woman with cervical cancer underwent intracavitary brachytherapy. Progress in the way that this cytotoxic agent is manipulated and delivered has seen an explosive growth over the past two decades with technological developments in physics, computing capabilities, and imaging. Although radiation oncologists are educated in and familiar with the wealth of new revolutionary techniques, it is not easy for other key members of the team to keep up with the rapid progress and its significance. However, to fully exploit these enormous gains and to communicate effectively, medical and gynecological oncologists are expected to be aware of state-of-the-art radiation oncology. Here, we elucidate and illustrate contemporary techniques in radiation oncology, with particular attention paid to the external beam radiotherapy used for adjuvant and primary definitive management of malignancies of the female pelvis.